GB18-06, a nanobody targeting GDF15, effectively alleviates weight loss and restores physical function in cachexia models - Yu Huang; Jinyong Wang; Xiling Wei; Hui Zhang; Wei Shang; Xiangling Zhang; Lanjiao Zhai; Xi Chen; Huiming Li; Suofu Qin (mAbs, 2024)
Cachexia is a complicated metabolic syndrome mainly associated with cancers, characterized by extreme weight loss and muscle wasting. It is a debilitating condition that negatively affects prognosis and survival. However, there is currently no effective pharmacological intervention that can reverse body weight loss and improve physical performance in patients with cachexia. Growth differentiation factor 15 (GDF15) can suppress appetite and regulate energy balance through binding to glial cell-derived neurotrophic factor receptor alpha-like (GFRAL). In order to develop a novel, effective treatment for cachexia, we generated a GDF15-targeting VHH nanobody, GB18–06, that was able to bind GDF15 with high affinity. In vitro, GB18–06 potently inhibited the GDF15-GFRAL signaling pathway, leading to a reduction of downstream ERK and AKT phosphorylation levels; in vivo, GB18–06 alleviated weight loss (>20%) in cancer and chemotherapy-induced cachexia models in mice. Compared with the control (phosphate-buffered saline) group, the ambulatory activity of mice in the GB18–06-treated group also increased 77%. Furthermore, GB18–06 exhibited desirable pharmacokinetic properties and an excellent developability profile. Our study has demonstrated a means of developing targeted treatment for cachexia with high efficacy, potentially leading to improved clinical outcomes and quality of life for patients with cachexia.